Adopting a design approach to translate needs and interests of stakeholders in academic entrepreneurship: The MIT Senseable City Lab case. (June 2017) - Simeone, Luca; Secundo, Giustina; Schiuma, Giovanni
Abstract: Recent research calls for greater consideration of design, by considering it further from the perspective of technology innovation management. In the attempt to cover this gap, the paper intends to explore how design can be used to support translational processes that connect and align different stakeholders in academic entrepreneurship. Insights from the investigation of the processes adopted by Senseable City Lab – an academic lab at MIT (Massachusetts Institute of Technology, USA) – will demonstrate how various design artefacts – sketches, visualizations, prototypes – are used to support several semiotic translations aimed at multiple stakeholders. Findings will show that design can play a relevant role in fostering entrepreneurial activities and value creation in academia, by supporting the translation of the different needs and interests of stakeholders into a shared meaning that allows a coordinated way of working. The conceptualization of design as a form of translation allows bridging currently distinct research strands in design and entrepreneurship. Highlights: Academic entrepreneurship relies upon the collaboration of diverse stakeholders. These stakeholders have different needs and interests and speak different languages. Design supports translation of different needs and interests into shared meaning. Design can enhance the alignment of stakeholders and support value creation. This paper bridges distinct research strands in design and entrepreneurship.